Cognitive Behavioral Therapy and Sleep Quality In Patients With Type 2 Diabetes Mellitus: A Review (HEALTH CARE: JURNAL KESEHATAN, 2026)
Sleep disturbances are highly prevalent among individuals with type 2 diabetes mellitus (T2DM) and are associated with adverse effects on glycemic control and quality of life. Cognitive behavioral therapy (CBT) and cognitive behavioral therapy for insomnia (CBT-I) are established non-pharmacological interventions; however, their effectiveness across specific sleep quality domains in this population remains insufficiently clarified. This review aimed to evaluate the effectiveness of CBT-based interventions across distinct sleep quality domains in individuals with T2DM. This review employed a narrative synthesis without meta-analysis (SWiM) approach to synthesize evidence on the effects of CBT/CBT-I on sleep quality in individuals with T2DM. The literature search was conducted using the PubMed, Scopus, EBSCOhost, and ProQuest databases. Sleep outcomes were categorized into six domains: overall sleep quality, sleep efficiency, sleep disturbances, sleep latency, sleep duration, and wake after sleep onset (WASO). Most studies reported significant improvements in overall sleep quality and sleep duration following CBT or CBT-I, with sustained benefits observed for up to 12 months post-intervention. In contrast, effects on sleep efficiency, sleep latency, sleep disturbances, and WASO were inconsistent and varied across studies. The effectiveness of CBT-based interventions appeared to be influenced by factors including session frequency, intervention duration, delivery modality, and patient engagement. CBT and CBT-I are effective in improving core aspects of sleep quality in individuals with T2DM, particularly when interventions are structured, sustained, and tailored to individual needs. Further large-scale, methodologically rigorous studies using standardized outcome measures are required to strengthen the evidence base and inform clinical practice.